"For them and for me": a qualitative exploration of peer befrienders' experiences supporting people with aphasia in the SUPERB feasibility trial. Issue 18 (28th August 2022) - Northcott, S.; Behn, N.; Monnelly, K.; Moss, B.; Marshall, J.; Thomas, S.; Simpson, A.; McVicker, S.; Flood, C.; Goldsmith, K.; Hilari, K.
Abstract: Purpose: Peer-befriending, where support is offered by someone with shared lived experience, is an intervention that may facilitate successful adjustment in people experiencing post-stroke aphasia. This paper explores the experiences of the peer-befrienders. Materials and methods: People with aphasia were recruited as peer-befrienders within the SUPERB trial investigating befriending for people with post-stroke aphasia. The intervention comprised six visits over three months. Peer-befrienders were matched with at least one befriendee and received training and ongoing supervision. They were invited to participate in in-depth interviews which were analysed using framework analysis. Results: All 10 befrienders participated in interviews, reporting on 19 matches. Seven main themes emerged: content of the sessions; befriender–befriendee relationship; negotiating the visits; handling boundaries and endings; positive impact of the befriending for befrienders and befriendees; and beliefs about the nature and value of peer support. While befrienders described challenges, such as negotiating journeys and witnessing distress, the role was perceived as a "secure challenge" due to the support and training received. Conclusions: Befrienders perceived the role as enjoyable and rewarding, and felt they were making a positive difference. They were unanimous in believing that people with aphasia can offer unique and valuable support to others with aphasia. Trial registration: ClinicalTrials.gov identifier NCT02947776, registered 28th October 2016. Implications for rehabilitation: People with lived experience of stroke and aphasia were able to offer emotional and social peer support to others with aphasia within the SUPERB trial. Although there were challenges, peer befrienders perceived the role as rewarding and satisfying. Peer befrienders valued the training and ongoing supervision and support they received to deliver the intervention. It is recommended that rehabilitation professionals considering offering peer-befriending schemes provide training and ongoing supervision to support peer-befrienders fulfil their role, as well as practical support with, e.g., arranging visits.